2021
DOI: 10.3389/fimmu.2021.781815
|View full text |Cite
|
Sign up to set email alerts
|

miR-223: An Immune Regulator in Infectious Disorders

Abstract: MicroRNAs (miRNAs) are diminutive noncoding RNAs that can influence disease development and progression by post-transcriptionally regulating gene expression. The anti-inflammatory miRNA, miR-223, was first identified as a regulator of myelopoietic differentiation in 2003. This miR-223 exhibits multiple regulatory functions in the immune response, and abnormal expression of miR-223 is shown to be associated with multiple infectious diseases, including viral hepatitis, human immunodeficiency virus type 1 (HIV-1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 123 publications
0
27
0
1
Order By: Relevance
“…It is noteworthy that miR-223 was first described as a regulator of myelopoietic differentiation in 2003, and to date, its multiple regulatory functions in the immune response are well documented. Abnormal expression of miR-223 is associated with multiple inflammatory diseases, including myocarditis, type II diabetes, acute lung injury, rheumatoid arthritis, and inflammatory bowel disease, as well as infectious diseases, including viral hepatitis, human immunodeficiency virus type 1 (HIV-1), and tuberculosis [ 113 ].…”
Section: The Role Of Micrornamentioning
confidence: 99%
“…It is noteworthy that miR-223 was first described as a regulator of myelopoietic differentiation in 2003, and to date, its multiple regulatory functions in the immune response are well documented. Abnormal expression of miR-223 is associated with multiple inflammatory diseases, including myocarditis, type II diabetes, acute lung injury, rheumatoid arthritis, and inflammatory bowel disease, as well as infectious diseases, including viral hepatitis, human immunodeficiency virus type 1 (HIV-1), and tuberculosis [ 113 ].…”
Section: The Role Of Micrornamentioning
confidence: 99%
“…The decreased expression of miR-486 in the present study may lead to minimal inflammatory response at 14 dpi and 21 dpi of S. japonicum infection. miR-223 is one of the differentially expressed miRNAs identified in our study that has been shown to play a vital role in the immune response, regulating multiple processes from myeloid differentiation to neutrophil, macrophage, and DC function (61). The changes of miR-223-3p expression are linked to macrophage apoptosis (62) and play an essential role in maintaining the balance of innate immunity to avoid excess inflammation and tissue damage.…”
Section: Discussionmentioning
confidence: 86%
“…Again, a large number of vertebrate studies have reported the majority of these miRNAs as responding to viral and bacterial infections [ 13 , 24 , 25 , 26 , 50 ]. Some of the miRNAs well-described as pathogen-responsive from the LS materials included miR-23 (apoptosis, angiogenesis, muscle growth and regeneration [ 13 , 50 , 75 , 76 ]), miR-223 (regulation of inflammation in response to infection or muscle regeneration [ 13 , 50 , 77 , 78 ]), miR-125 and miR-146 (both annotated as viral as well as bacterial infection-responsive [ 13 , 32 , 50 ]) and miR-7132 (teleost-specific infection-responsive [ 25 ]). Two others of these gDE-miRNAs; miR-144 and miR-451 are expressed from a conserved miRNA gene cluster [ 17 ].…”
Section: Discussionmentioning
confidence: 99%